Losses Associated with Secondary Effects in Earthquakes - Daniell, James E.; Schaefer, Andreas M.; Wenzel, Friedemann (Frontiers in Built Environment, 2017)
The number of earthquakes with high damage and high losses has been limited to around 100 events since 1900. Looking at historical losses from 1900 onwards, we see that around 100 key earthquakes (or around 1% of damaging earthquakes) have caused around 93% of losses. What is indeed interesting about this statistic is that within these events, secondary effects have played a major role, causing around 40% of economic losses and fatalities as compared to shaking effects. Disaggregation of secondary effect economic losses and fatalities demonstrating the relative influence of historical losses from direct earthquake shaking in comparison to tsunami, fire, landslides, liquefaction, fault rupture and other type losses is important if we are to understand the key causes post-earthquake. The trends and major event impacts of secondary effects are explored in terms of their historic impact as well as looking to improved ways to disaggregate them through two case studies of the Tohoku 2011 event for earthquake, tsunami, liquefaction, fire and the nuclear impact; as well as the Chilean 1960 earthquake and tsunami event.